Generation of high-dimensional qudit quantum states via two-dimensional quantum walks - Chiara Esposito; Francesco Di Colandrea; Francesco Hoch; Gonzalo Carvacho; Filippo Cardano; Nicolò Spagnolo; Lorenzo Marrucci; Fabio Sciarrino (Physical Review Research, 2023)
Several quantum protocols, with applications ranging from fundamental studies to cryptographic scenarios, can be enhanced through the generation and manipulation of quantum states that belong to high-dimensional Hilbert spaces. For this reason, it is worth devoting efforts to find more efficient methods for complex qudit-state generation. One-dimensional quantum walks have proved to be efficient and versatile platforms for the engineering of such complex states. Hitherto, however, using their two-dimensional counterpart for this task has remained unexplored. In this paper, we consider two-dimensional quantum walk evolution as a tool for the generation of high-dimensional qudit states. We theoretically prove that a suitable change of the coin operators at each step permits the generation of a subset of qudit states by using less resources with respect to the one-dimensional counterpart. Then, we successfully generate qudit states by exploiting two-dimensional quantum walks on an experimental photonic platform. The walker position is encoded on discrete sets of optical modes carrying quantized amounts of transverse momentum and the mode couplings are actively controlled via liquid-crystal devices. The obtained results provide insight into qudit generation for applications in quantum communication and quantum cryptography.